The Effect of Length and Content of Fiber on Glass Fiber and Basalt Fiber-Reinforced Granite Residual Soil - Weijie Chen; Jin Zhao; Litao Fan; Jia Li; Bingxiang Yuan; Hongzhong Li; Guoping Jiang; Hanbo Li; Tianying Chen (Advances in Civil Engineering)
Fiber-reinforced soil boasts fewer cracks, higher energy absorption, and higher residual strength. With the well-established concept of carbon neutralization, it is necessary to reduce the dependence on high carbon-emitting reinforcement materials such as cement and concrete. The need for resource recycling has led to the development of reusing construction waste as the raw material for slope and embankment reinforcement. The purpose of this study is to analyze the reinforcement performance and environmental feasibility of glass and basalt fiber on granite residual soil with the content of 3%, 4%, and 5% and the length of 6 mm, 9 mm, and 12 mm. The reinforced samples were subjected to static impact load tests and SEM analysis to study its mechanical properties, microcharacteristics, and structure before and after reinforcement. Results show that the incorporation of 3% glass fibers of 6 mm has the best reinforcement effect on GRS, while the incorporation of 4% basalt fibers of 6 mm also has a good reinforcement ability. Glass fiber performs better than basalt fiber under the optimal content and length. SEM results indicate that glass fibers bind the soil particles more closely, thereby increasing their friction and leading to higher compressive strength. When the length and content of fiber exceed a certain range, the fibers are prone to cross and knot and fail to fill between soil particles, so the fiber and soil particles are separated, which lowers the strength of the soil. It is concluded that both glass fiber and basalt fiber can be well used for reinforcing GRS for higher bearing capacity and fewer cracks at the given proportion and length. Fiber length and content were considered when reinforcing GRS with different fibers in this study.